Perancangan Video Profil SD Negeri 3 Bentangan Sebagai Media Promosi dan Informasi - Theo Hendrawan Tama; Daniel Rudjiono; Agus Priyadi (UNIVERSITAS STEKOM, 2026)
This study aimed to develop a profile video as a promotional and informational medium for State Elementary School 3 Bentangan and to evaluate its feasibility level. The problem was initiated by the school's continuous reliance on print media, such as brochures, and the urgent need for digital content suitable for social media platforms to reach the wider community. To address this, the Research and Development method was employed, utilizing seven stages of development procedures. Data were collected through questionnaires and analyzed using a Likert Scale. The profile video development was validated by media and material experts, and subsequently tested by users. The research results indicated that the developed profile video was highly feasible for use as a promotional and informational medium, based on the validation tests conducted by the media experts, material experts, and users.